Dimensi Fiqh Jinayah Pada KUHPidana Tentang Perzinaan - Herlina Safitri & Ikhwanuddin Harahap & Dermina Dalimunthe (Jurnal El-Thawalib, 2020)
Adultery is a serious problem faced by Islam, including in the State of Indonesia. In Indonesian legal regulations, zina is regulated in Article 284 Paragraph 1 of the Criminal Code, where the concept of zina which is described in this article is different from that described in the concept of Islamic Law or fiqh jinayah. The formulation of the problem of this research is how the act of adultery in the Criminal Code and Jinayah fiqh, what are the criteria for adultery perpetrators in the Criminal Code and Jinayah fiqh and how are the sanctions for adultery perpetrators in the Criminal Code and Jinayah fiqh. The purpose of this study was to determine the adultery act in the Criminal Code and Jinayah fiqh, to determine the criteria for adultery in the Criminal Code and Jinayah fiqh and to determine the sanctions for adultery in the Criminal Code and Jinayah fiqh. The theory used in this research is the theory regarding the concept of adultery in jinnayah fiqh and the concept of adultery in Article 284 Paragraph 1 of the Criminal Code. Furthermore, the type of research used is library research, using a normative juridical approach. The results of the research obtained show that the act of adultery in Article 284 Paragraph 1 of the Criminal Code provides three essential conditions to be said to be an act of adultery, as well as jinnayah fiqh which provides three pillars of adultery. The perpetrator of adultery in Article 284 Paragraph 1 of the Criminal Code is different from the perpetrator of adultery in jinnayah fiqh, in Article 284 Paragraph 1 of the Criminal Code only applies to pairs of adulterers who are married and have intercourse not with their legal partner and there is no determination of the perpetrator's age, whereas in fiqh jinayah the perpetrator Adultery is stipulated for people who are married and people who are not married and people who are in their age of maturity are determined as adulterers. Whereas the sanctions for adultery perpetrators in Article 284 Paragraph 1 of the Criminal Code are very light when compared to the punishment for adultery in jinnayah fiqh, imprisonment given to adultery perpetrators which is one of the criminal sanctions for ta'zir in fiqh jinayah, and the perpetrators who commit adultery with qualifications who have been married are designated as criminals and are given sanctions